(3eSGdc GdGagGe Edi TQGFY GdESdGes - (3GdYGedj, GdLYHj, YR GdOjf, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g`s
(3ChdgG (B:s
(3bhdg(B: (3hKjbI dOjf GdeQJgf(B. (3GdQgf dZI GdKHhJ hGdOhGe(B. (3jbGd(B: (3Qgf GdTjA EPG KHJ hOGe(B...s
(3BNQgG (B:s
(3hjMJed HWdGf GdfcGM dHWdGf YJb HYVgG Ydi cd JbOjQ hdCfg dh UM dhLH GdeSei EP GdebJVi dHWdGf GdeSei gh Jhbag Ydi UMI GdfcGM GdeJbOes
(3JHUQI GdeDda (B:s
(3GdTgjQ HGdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
(3GdPQjYI HQbe(B: 3516s
(3GdCYdGe(B: (3L(B3(3, U(B64s
Keywords: (3abg GdePGgH GdCNQis